2017
DOI: 10.1097/md.0000000000007024
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D supplementation and disease activity in patients with immune-mediated rheumatic diseases

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
57
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 53 publications
1
57
1
4
Order By: Relevance
“…Previous studies of the relation among disease activity and vitamin D levels in RA participants demonstrated conflicting findings [19]. Our study demonstrated that serum vitamin D concentrations were not connected with disease activity, its individual objective and subjective components, inflammatory markers, RF and anti-CCP seropositivity, and radiological damage scores.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Previous studies of the relation among disease activity and vitamin D levels in RA participants demonstrated conflicting findings [19]. Our study demonstrated that serum vitamin D concentrations were not connected with disease activity, its individual objective and subjective components, inflammatory markers, RF and anti-CCP seropositivity, and radiological damage scores.…”
Section: Discussioncontrasting
confidence: 68%
“…In countries near equator, where humans synthesize vitamin D on their skin for longer periods during the year, the low incidence of rheumatic disease prompted to research the role of vitamin D on the existence of rheumatic diseases [19]. Besides, an experimental study in 1998 showed that vitamin D receptor agonists reduced disease expression and worsening of arthritis [20].…”
Section: Discussionmentioning
confidence: 99%
“…Contradictory to these findings, a study in the Indian population observed improvement in RA disease activity following treatment with loading dose of vitamin D . A meta‐analysis performed for RA reported that an insignificant reduction in RA recurrence was seen after vitamin D supplementation in two studies while there was no statistical significance in DAS28 reduction in another two studies …”
Section: Discussionmentioning
confidence: 99%
“…Varenna, et al reported that vitamin D supplementation may be recommended for RA patients for the prevention and treatment of osteoporosis as well as for its possible effects on disease activity [44]. Franco, et al concluded in a meta-analysis that vitamin D supplementation could possibly reduce rheumatoid arthritis recurrence [45].…”
Section: Discussionmentioning
confidence: 99%